Enrollment of women in STEM - Mariana ROBU (Eastern European Journal of Regional Studies)
The aim of this research is to contribute to the development of national policies and strategies for attracting and guiding women in STEM education programs of the Republic of Moldova. The research method is based on national data analyses, statistical trends and econometric forecasting analyses to identify the benefits of increasing the representation of women in STEM areas. The key conclusions are that the enrollment of women in research and education in area of STEM (Science, Technology, Engineering and Mathematics) will contribute to the economic development of a country. The paper presents concrete economic benefits from increasing the number of women in STEM, from creation of new employment to the economic development of the country and in particular in STEM areas.